Educational Motivation and Self-Efficacy as Factors in the Formation of Academic Success of Students - Galyna Kovalchuk; Yaroslav Semyonov (Pedagogical Discourse, 2024)
The problem of the formation and development of educational motives in the study of professional disciplines has become more and more relevant in recent years, as more and more often researchers point to the decrease in the effectiveness of traditional education in institutions of higher education, especially in the conditions of war in Ukraine. In the course of our research, it was established that educational motivation is one of the main factors in increasing academic success and forming the self-efficacy of education seekers - students in the process of professional education.As a result, a decrease in educational motivation leads to the insufficient formation of professionally significant competencies and skills, in particular, self-organization, responsibility, and the ability to self-directed learning. Therefore, the formation and development of educational motivation of education seekers is among the most important tasks in terms of increasing academic success and the overall effectiveness of education. The structure of educational motivation and the dominant motives of educational and cognitive activity significantly affect the general academic success and cognitive activity of students during classroom training and their attitude to independent (individual) work. The teacher is faced with the task of developing a system of didactic methods and tools for creating an environment conducive to learning and forming the educational motivation of students.Researchers note that the student's motivational sphere in the process of obtaining an education is quite dynamic and flexible, and is determined by various social influences in a specific historical environment. Therefore, the teacher has the opportunity to choose and model various didactic tools for the development of educational motivation of students in the process of studying professional engineering and psychological-pedagogical disciplines.